Cerebellar transcranial alternating current stimulation in the gamma range applied during the acquisition of a novel motor skill - Wessel, Maximilian J.; Draaisma, Laurijn R.; de Boer, Anne F. W.; Park, Chang-hyun; Maceira-Elvira, Pablo; Durand-Ruel, Manon; Koch, Philipp J.; Morishita, Takuya; Hummel, Friedhelm C. (Scientific reports, 2020)
The development of novel strategies to augment motor training success is of great interest for healthy persons and neurological patients. A promising approach is the combination of training with transcranial electric stimulation. However, limited reproducibility and varying effect sizes make further protocol optimization necessary. We tested the effects of a novel cerebellar transcranial alternating current stimulation protocol (tACS) on motor skill learning. Furthermore, we studied underlying mechanisms by means of transcranial magnetic stimulation and analysis of fMRI-based resting-state connectivity. N = 15 young, healthy participants were recruited. 50 Hz tACS was applied to the left cerebellum in a double-blind, sham-controlled, cross-over design concurrently to the acquisition of a novel motor skill. Potential underlying mechanisms were assessed by studying short intracortical inhibition at rest (SICI rest ) and in the premovement phase (SICI move ), intracortical facilitation at rest (ICF rest ), and seed-based resting-state fMRI-based functional connectivity (FC) in a hypothesis-driven motor learning network. Active stimulation did not enhance skill acquisition or retention. Minor effects on striato-parietal FC were present. Linear mixed effects modelling identified SICI move modulation and baseline task performance as the most influential determining factors for predicting training success. Accounting for the identified factors may allow to stratify participants for future training-based interventions.